Speed Measurement for Three-Phase Induction Motor Drive Based on Arduino Uno - Haris, Muhammad; Mursyidin (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2025)
This study aims to design and test a three-phase induction motor speed measurement device based on Arduino Uno. Three-phase induction motors are often used in industry because of their reliability, high efficiency, and easy maintenance. However, these motors have weaknesses, namely low starting torque and difficulty in regulating speed, which can cause operational instability. Therefore, this study developed an Arduino Uno-based control system capable of regulating motor speed by changing the frequency of the electrical supply. This research is quantitative in nature and uses an experimental method. The results of the study show that the designed device is capable of improving the stability and operational efficiency of three-phase induction motors. The use of an LM393 speed sensor aligned with the motor rotor allows the system to respond to load changes in real-time, maintain a constant speed, and reduce energy consumption. Based on these results, it can be concluded that the development of an Arduino Uno-based speed measurement device is effective in addressing the challenges of controlling the speed of a three-phase induction motor and has broad application potential in industry.